Implementasi Program Penarikan Alat Kesehatan Bermerkuri Di Puskesmas Kecamatan Sukmajaya - Elza Muthia Septanti; Tri Joko; Nurjazuli Nurjazuli (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
The healthcare sector is one of the most important sources of mercury emissions worldwide due to its use in medical devices. Hg is found in thermometers, sphygmomanometers, and dental amalgams. Risk factors due to mercury can arise if medical devices containing mercury are damaged, broken, or spilled. The Government of Indonesia issued Regulation of the Minister of Health Number 41 of 2019 concerning the Elimination and Withdrawal of Mercury Medical Devices in Health Service Facilities. The purpose of this study was to evaluate the withdrawal program for mercury medical devices in Puskesmas in Sukmajaya District, namely Abadijaya Health Center, Baktijaya Health Center, Pondok Sukmajaya Health Center, and Sukmajaya Health Center. Research on the evaluation of the program for the elimination of mercury medical devices in the community health center of Sukmajaya District was conducted using a descriptive observational research design with a quantitative approach. The Mercury Medical Device Withdrawal Program at the Sukmajaya District Community Health Center has not been 100% successful. All puskesmas have stopped using mercury medical devices and switched to non-mercury medical devices, but the management carried out by the puskesmas has not met the requirements because there are still stocks of mercury medical devices that are not available. According to the standard, The withdrawal of mercury medical devices has also not been carried out by the Health Office, and the guidance and supervision of the program also does not run according to standards.